Hydroxytyrosol Benefits Boar Semen Quality via Improving Gut Microbiota and Blood Metabolome - Han, Hui; Zhong, Ruqing; Zhou, Yexun; Xiong, Bohui; Chen, Liang; Jiang, Yue; Liu, Lei; Sun, Haiqing; Tan, Jiajian; Tao, Fuping; Zhao, Yong; Zhang, Hongfu (Frontiers in Nutrition, 2022)
Semen quality is one of the most important factors for the success of artificial insemination which has been widely applied in swine industry to take the advantages of the superior genetic background and higher fertility capability of boars. Hydroxytyrosol (HT), a polyphenol, has attracted broad interest due to its strong antioxidant, anti-inflammatory, and antibacterial activities. Sperm plasma membrane contains a large proportion of polyunsaturated fatty acids which is easily impaired by oxidative stress and thus to diminish semen quality. In current investigation, we aimed to explore the effects of dietary supplementation of HT on boar semen quality and the underlying mechanisms. Dietary supplementation of HT tended to increase sperm motility and semen volume/ejaculation. And the follow-up two months (without HT, just basal diet), the semen volume was significantly more while the abnormal sperm was less in HT group than that in control group. HT increased the “beneficial microbes” Bifidobacterium, Lactobacillus, Eubacterium, Intestinimonas, Coprococcus, and Butyricicoccus, however, decreased the relative abundance of “harmful microbes” Streptococcus, Oscillibacter, Clostridium_sensu_stricto, Escherichia, Phascolarctobacterium, and Barnesiella. Furthermore, HT increased plamsa steroid hormones such as testosterone and its derivatives, and antioxidant molecules while decreased bile acids and the derivatives. All the data suggest that HT improves gut microbiota to benefit plasma metabolites then to enhance spermatogenesis and semen quality. HT may be used as dietary additive to enhance boar semen quality in swine industry.